Regulators of G protein Signaling (RGS) proteins (version 2019.4) in the IUPHAR/BPS Guide to Pharmacology Database (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
Regulators of G protein signalling (RGS) proteins display a common RGS domain that interacts with the GTP-bound Gα subunits of heterotrimeric G proteins, enhancing GTP hydrolysis by stabilising the transition state [29, 419, 418], leading to a termination of GPCR signalling. Interactions through protein:protein interactions of many RGS proteins have been identified for targets other than heteromeric G proteins. Sequence analysis of the 20 RGS proteins suggests four families of RGS: RZ, R4, R7 and R12 families. Many of these proteins have been identified to have effects other than through targetting G proteins. Included here is RGS4 for which a number of pharmacological inhibitors have been described.